Local Communities' Involvement in Ecotourism around Tanjung Datu National Park : Potentials and Challenges - Wan Sofiah, Meor Osman; Wan Robiah, Meor Osman; Rosita, Hamdan; Muhammad Asraf, Abdullah; Wong, Swee Kiong; Bistari, Mahmood (2019)
The aim of this paper is to explore the potentials and challenges of local communities' involvement in ecotourism around Tanjung Datu National Park (TDNP). Using three separate interviews, this qualitative study involved three major entities participated in ecotollrism activities around Tanjung Datu National Park (TDNP). Interviews were conducted among the local communities (17 participants) and business owners (7 participants) from two villages located at the vicinity of TDNP namely Kg. Telok Serabang and Kg. Telok Melano, and both local and international tourists (19 participants) who visited TDNP. The findings from the preliminary data indicate that ecotourism around TDNP has indirectly contributed to livelihoods of local communities and there are potentials and challenges in terms of communities' involvement/or the tourism-based economy to sustain itself.